Raspberry Pi-Based Offline Digital Library for Indonesian Villages Without Stable Power and Internet Access: A Case Study on Implementing Raspberry Pi-Based Offline Digital Library in Indonesia. - Santo Wiguna, Edward Evannov; Lie, Hendry; Niro, Lorenzo; Linggarjati, Jimmy; Atmadja, Wiedjaja; Hutabarat, Daniel Patricko; Alexander, Ivan; Susanto, Rudy; Yapson, Johan; Reigton Hartono, John; Pardede, Marincan; Wishnoebroto; et al. (Information Technology & Libraries, 2024)
As one of the world's largest archipelagic nations, Indonesia faces a major challenge in distributing its wealth, including basic infrastructure such as electricity and internet, to some of its most remote islands. Due to its remote location, most people in this area live in poverty and have poor-quality education. To help solve this problem, an offline digital library was created based on a Raspberry Pi "minicomputer." With the ability to store more than 2,500 educational movies and e-books for offline viewing, the device has proven to be reliable even in areas with unpredictable power.